PENGEMBANGAN MOTIF BATIK KANAKA UNTUK SERAGAM PPI ISHIKAWA JEPANG - Morinta Rosandini; Hafiza Aprilia (Institut Seni Indonesia Yogyakarta, 2021)
PPI Ishikawa, Japan has a jacket uniform, but this uniform doesn’t have a strong Indonesian visual identity yet in it. The Kanaka Batik which was the winner in the batik design contest held by PPI Ishikawa, Japan to be made a uniform hasn’t been realized due to the difficulty of producing the batik. Therefore the purpose of this design is to design the PPI Ishikawa, Japanese uniform by applying the Kanaka Batik motif that has been developed by applying the digital printing and embroidery techniques. The stage of the design method is in the form of problem analysis and problem solving strategies. Then the result of this are three designs of developing Kanaka Batik motifs on a fabric measuring 90 x 100 cm and one sketch of a uniform design of a jacket with the development of Kanaka Batik motifs in it. Through this paper it’s hoped that it can add references for the readersPPI Ishikawa Jepang memiliki seragam berupa jaket, namun seragam ini belum memiliki identitas visual Indonesia yang kuat di dalamnya. Adapun Batik Kanaka yang menjadi pemenang dalam sayembara desain batik yang diadakan oleh PPI Ishikawa Jepang untuk dijadikan seragam belum direalisasikan karena kesulitan memproduksi batik tersebut. Maka dari itu tujuan perancangan ini ialah untuk merancang seragam PPI Ishikawa Jepang dengan mengaplikasikan motif Batik Kanaka yang telah dikembangkan dengan penerapan teknik digital printing dan bordir. Tahapan metode perancangan ini berupa analisis permasalahan dan strategi pemecahan masalah. Kemudian hasilnya adalah tiga desain pengembangan motif Batik Kanaka pada kain berukuran 90 x 100 cm dan satu sketsa desain seragam jaket dengan pengembangan motif Batik Kanaka di dalamnya. Melalui karya tulis ini diharapkan dapat menambah referensi bagi para pembaca.